2018
DOI: 10.1002/ijc.31936
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of somatically acquired and constitutive uniparental disomy in gastrointestinal cancers

Abstract: Somatically acquired uniparental disomies (aUPDs) are frequent events in solid tumors and have been associated with cancer‐related genes. Studies assessing their functional consequences across several cancer types are therefore necessary. Here, we aimed at integrating aUPD profiles with the mutational status of cancer‐related genes in a tumor‐type specific manner. Using TCGA datasets for 1,032 gastrointestinal cancers, including colon (COAD), rectum (READ), stomach (STAD), esophageal adenocarcinoma (EAC) and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 60 publications
0
5
1
1
Order By: Relevance
“…In this study, we employed SNP-A to assess cnLOH profiles in SCRC among all cases and by subgroup classification in order to better understand etiologies underlying sporadic colorectal carcinogenesis. Previous reports have analyzed cnLOH profiles across diverse gastrointestinal tumors and revealed the lowest level of regions with cnLOH (3 per sample) for colon cancers by tumor type [10]. Nevertheless, compared with previous results, our specific interrogation of SCRCs revealed a higher frequency of regions altered by cnLOH (median of 7.5 events per sample).…”
Section: Discussioncontrasting
confidence: 44%
See 2 more Smart Citations
“…In this study, we employed SNP-A to assess cnLOH profiles in SCRC among all cases and by subgroup classification in order to better understand etiologies underlying sporadic colorectal carcinogenesis. Previous reports have analyzed cnLOH profiles across diverse gastrointestinal tumors and revealed the lowest level of regions with cnLOH (3 per sample) for colon cancers by tumor type [10]. Nevertheless, compared with previous results, our specific interrogation of SCRCs revealed a higher frequency of regions altered by cnLOH (median of 7.5 events per sample).…”
Section: Discussioncontrasting
confidence: 44%
“…Nevertheless, compared with previous results, our specific interrogation of SCRCs revealed a higher frequency of regions altered by cnLOH (median of 7.5 events per sample). We also observed that SCRCs showed a distinct pattern of cnLOH events compared with cases with one primary invasive CRC [10]. It is important to note that while previous studies have leveraged similar techniques and cnLOH criteria, the biospecimen type (e.g.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Применение CGH предоставило доказательства того, что геномный дисбаланс ответственен за прогрессирование опухоли от диспластических поражений до инвазивного заболевания. Позже ДНК-микрочипы позволили одновременно измерить количество копий многих полиморфных локусов в геноме, что привело к обнаружению с высоким разрешением LOH, обычного явления в онкогенезе [27].…”
Section: стратегии и подходы к анализу изменений числа копий генов пр...unclassified
“…Recent reports have shown that aUPD events are non-randomly distributed across cancer types, pointing out common genomic profiles of aUPD in a tumor-type specific manner, which typically coincide with regions of genomic losses, both in solid tumors and hematological malignancies [5, 6]. In addition, the identification of cancer-specific minimal regions of aUPD has led to the discovery of inactivating mutations in cancer-related genes, which might increase the functional relevance of such events in the development of cancer.…”
mentioning
confidence: 99%